Educación y comunicación en el libro I de la República de Platón - Pascual, L.C., Fernando (Alpha Omega, 2022)
Summary: This article seeks to highlight some elements of the theory of education and communication present in Book I of Plato’s Republic, first in an analytical way (as these elements appear throughout the narrative), and then in an attempt at synthesis. Sommario: Questo articolo cerca di mettere in evidenza alcuni elementi della teoria dell’educazione e della comunicazione presenti nel Libro I della Repubblica di Platone, prima in modo analitico (così come questi elementi appaiono lungo la narrazione), e poi in un tentativo di sintesi.